SIRT1 regulates metabolism and leukemogenic potential in CML stem cells - Abraham, Ajay; Qiu, Shaowei; Chacko, Balu K.; Li, Hui; Paterson, Andrew; He, Jianbo; Agarwal, Puneet; Shah, Mansi; Welner, Robert; Darley-Usmar, Victor M.; Bhatia, Ravi (The Journal of Clinical Investigation, 2019)
Chronic myeloid leukemia (CML) results from hematopoietic stem cell transformation by the BCR-ABL kinase. Despite the success of BCR-ABL tyrosine kinase inhibitors (TKIs) in treating CML patients, leukemia stem cells (LSCs) resist elimination and persist as a major barrier to cure. Previous studies suggest that overexpression of the sirtuin 1 (SIRT1) deacetylase may contribute to LSC maintenance in CML. Here, by genetically deleting SIRT1 in transgenic CML mice, we definitively demonstrated an important role for SIRT1 in leukemia development. We identified a previously unrecognized role for SIRT1 in mediating increased mitochondrial oxidative phosphorylation in CML LSCs. We showed that mitochondrial alterations were kinase independent and that TKI treatment enhanced inhibition of CML hematopoiesis in SIRT1-deleted mice. We further showed that the SIRT1 substrate PGC-1α contributed to increased oxidative phosphorylation and TKI resistance in CML LSCs. These results reveal an important role for SIRT1 and downstream signaling mechanisms in altered mitochondrial respiration in CML LSCs.